2014
DOI: 10.1111/pim.12124
|View full text |Cite
|
Sign up to set email alerts
|

Comparative profile of circulating antigenic peptides in CSF, serum & urine from patients with neurocysticercosis diagnosed by immunoblotting

Abstract: Traditionally serum and/or CSF specimens have been used for detection of either specific antibodies or antigens as a supportive diagnosis of NCC. However, in recent days, much interest has been shown employing noninvasive specimens such as urine. In our study, we identified and compared a profile of circulating antigenic peptides of parasite origin in three different body fluids (CSF, serum and urine) obtained from confirmed NCC cases and control subjects. The circulating antigenic peptides were resolved by SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Others have noted the ability to detect Taenia antigens in the urine of patients with NCC [ 15 ]. Urine antigen levels have been observed to correlate with viable cyst burden [ 16 ], and detection has been used as a population screening tool for subarachnoid disease in Peru [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Others have noted the ability to detect Taenia antigens in the urine of patients with NCC [ 15 ]. Urine antigen levels have been observed to correlate with viable cyst burden [ 16 ], and detection has been used as a population screening tool for subarachnoid disease in Peru [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…A comparative study of antigenic peptides in three different body fluids (CSF, serum, and urine) obtained from confirmed NCC cases and control subjects found that only lower molecular weight antigenic peptides were found in urine, whereas higher molecular weight antigenic peptides were found in serum and CSF. 54 Also, somatic as well as excretory antigens were detected with highest sensitivity in the CSF specimen followed by serum and urine. The highest efficacy overall (90%–91%) for detecting antigens was in the CSF.…”
Section: Antigen Detection Testsmentioning
confidence: 95%